Роль единиц сленга в обогащении словарного состава современного английского языка - Крылова, Д.А.; Петренко, А.Д. (Культура народов Причерноморья, 2014)
В данной статье исследованы дискурсивные особенности сленга в современном английском
языке, выявлены языковые особенности сленга, рассмотрено использование сленга в англоязычной
художественной литературе, изучено формирование и функционирование единиц сленга, выявлена роль
языковых единиц сленга в современном английском языке. Выбор темы исследования обусловлен малой
степенью изученности проблемы. Это объясняется тем, что большинство исследований сленга строго
ограничено и находится в определенных рамках, при этом не делается попыток лингвистических
обобщений или выводов. У даній статті досліджені дискурсивні особливості сленгу в сучасній англійській мові,
виявлені мовні особливості сленгу, розглянуто використання сленгу в англомовній художній літературі,
досліджено формування та функціонування одиниць сленгу, виявлена роль мовних одиниць сленгу в
сучасній англійській мові. Вибір теми дослідження зумовлений малим ступенем вивченості проблеми. Це
пояснюється тим, що більшість досліджень сленгу суворо обмежена і знаходиться в певних рамках, при
цьому не робиться спроб лінгвістичних узагальнень або висновків. The discursive features of slang in modern English, linguistic features of computer and youth slang,
the use of slang in the English-language literature, the formation and functioning of slang units, and the role of
slang units in the enrichment of the modern English vocabulary were investigated in the research work. The
choice of research topic is determined by the low degree of scrutiny of the problem. This is explained by the fact
that the most studies of slang are strictly limited and are within certain limits, with no attempt to linguistic
generalizations or conclusions.
The relevance of the topic is conditioned for the interest of scientists to the issue, the need for a comprehensive
study of the phenomenon. The basic methods were the comparative-historical method, component analysis and
modeling of word composition. The material for the selection of lexical units are the articles, journals,
dictionaries Partridge E.A. Dictionary of Slang and Unconventional English, Dictionary of contemporary slang
ed. by T. E. Thorne, The Macmillan Dictionary of Contemporary Phrase and Fable.
The practical significance of this work lies in the possibility of applying the results of research in lexicology, on a
practical course of English. The theoretical significance of this work lies in the fact that it is a contribution to the
further development of functional lexicology.